Wohnmobilität im Alter - ein zukunftsfähiger Ansatz für die Siedlungsentwicklung nach innen? - Zimmerli, Joëlle (Routledge, 2016)
Der Artikel geht folgenden Fragen nach: Gesellschaftliches Potenzial: Wie verändert sich die Wohnmobilität im Alter mit der ins Pensionsalter tretenden Generation der Baby-boomer? Ursache und Anlass: Was kann die Generation der Babyboomer dazu veranlassen im Alter umzuziehen, und welche raumtypologischen Zusammenhänge zeigen sich? Planung: Mit welchen planerischen Rahmenbedingungen kann eine stärkere Umzugsdynamik im Alter unterstützt werden? Die forschungsleitende Hypothese, die für ein grösseres Umzugspotenzial in der künftigen älteren Generation spricht, lautet, dass Baby-boomer im Alter andere Wohnpräferenzen haben werden als ihre heute alten- Eltern. Diese Annahme stützt sich einerseits auf die veränderten gesellschaftlichen und wirtschaftlichen Rahmenbedingungen, unter denen Baby-boomer sozialisiert worden sind.

When planners debate settlement density, residential mobility typically gets short shrift: conventional wisdom holds that people want to stay where they are. Unsurprisingly, therefore, demographic change is often framed as a burden: an ever larger cohort of ever older people live ever longer in family dwellings, exacerbating pressures on land use. Yet the residential preferences of ageing baby boomers suggest that change is often welcome, and that demography can be an opportunity for a more sustainable use of built-up areas. To empirically ground the often emotional debate about a more efficient use of the housing stock, the author conducted a representative survey of 1200 people, aged 50-87, in the Cantons of Aargau and Zurich in 2011. Contrary to widely held beliefs, 43% of respondents said they could envisage moving: to purchase real estate, to upgrade residential qualities or location, and to reduce space and housework. Add to this the desire to remain mobile, and to remain independent, and it is clear that the will for selfdetermination bears a huge potential for consolidation: according to one calculation, the two cantons could forego four years of residential building over the next 25 years if they tapped the relocation potential of the elderly. Yet relocations do not just happen: people move if they have attractive alternatives to existing residential solutions, and if supply responds to regional markets and if it meets the elderly's needs. To create a planning environment that is conducive to the development of such alternatives, planners do not need more expansive job descriptions. What is needed are cooperative planning processes that give economists and social scientists an early say. Inward development and residential consolidation do not simply call for revised plans and regulations; they need sensible and empirically grounded analyses of the social dynamics and the economic conditions that help and hinder a more efficient and user-friendly use of the building stock.
Residential mobility of the elderly - A sustainable approach to higher residential density?
Keywords: Stadtplanung; Stadtforschung; Mobilität; Alter Mensch; Wohnstandort; Umzug; Wohnwunsch; Siedlungsentwicklung; Wohnmobilität; Wohnpräferenz; Demographischer Wandel; Rahmenbedingung; Innenentwicklung; Nachverdichtung